Evaluation of cross-protection of African swine fever vaccine ASFV-G-ΔI177L between ASFV biotypes - Borca, M.V.; Ramirez-Medina, E.; Mutisya, Christine; Ojuok, Rose; Odaba, Josiah; Dihbol, M.; Lacasta, Anna; Gladue, D.P. (MDPI, 2025)
Background/Objectives: Vaccine development for the prevention of ASF has been very challenging due to the extensive genetic and largely unknown antigenic diversity. Inactivated vaccines, using different inactivation methods and a variety of adjuvants, have been consistently inefficacious. Historically, animals recovering from an infection with an attenuated virus became protected from the development of a clinical disease caused by an antigenically related strain. Therefore, immunization of susceptible animals with attenuated virus strains has become a common method of vaccination with the first two commercially available vaccines based on recombinant live-attenuated viruses (LAVs). An important limitation is that the efficacy of the LAV is restricted to those strains that are antigenically related and, in most cases, only provide protection against homologous strains. Due to the unknown antigenic heterogeneity among all ASFV field isolates, the development of broad-spectrum vaccines is a challenge. Besides the anecdotal data, there is not a large amount of information describing patterns of cross-protection between different ASFV strains.